Evaluation and Selection of Bromegrass Genotypes under Phosphorus and Water Scarcity towards the Development of Resilient Agriculture Focusing on Efficient Resource Use - Sebastián Meier; Pedro M. de Souza Campos; Arturo Morales; Rafael López-Olivari; Fernando Ortega-Klose; Humberto Aponte; Paula Cartes; Naser Khan; Gabrijel Ondrasek; Pamela Cea; Rubén Palma-Millanao; Alex Seguel (Agronomy, 2024)
The relationship between phosphorus (P) availability and water restriction was explored in this study, focusing on its impact on phosphorus use efficiency (PUE) and water use efficiency (WUE) in various bromegrass (Bromus spp.) genotypes. Under controlled conditions, five bromegrass genotypes, as well as one ryegrass (Lolium perenne) cultivar, were compared by subjecting them to two P levels and two watering regimes. It was determined that combining water and phosphorus limitations led to reduced plant productivity. Initially, the ryegrass outperformed the bromegrass, but this result declined over time, while bromegrass exhibited consistent stability. Notably, under P and water stress, enhanced root development was observed in bromegrass compared to that in ryegrass. Distinct patterns of PUE and WUE allowed for the categorization of bromegrass genotypes into three groups. Genotype 3457 emerged as the most efficient, scoring 20 out of 24, while Pro 94-49 A achieved a score of only 10 out of 24. This study suggests that the drought resilience of bromegrass may be linked to increased root growth during the early vegetative stages, which potentially facilitates improved P acquisition. However, further validation through long-term field experiments is needed. The insights from this study are potentially valuable for use in shaping plant breeding programs by revealing the plant adaptation mechanisms for both P and water absorption.